POLICY ANALYSIS OF MSME DEVELOPMENT AS A SUPPORT FOR ECONOMIC DEVELOPMENT IN SIDOARJO REGENCY - Oktaviani, Ailsyah Putri; Ramadani, Tutut Putri (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
In the era of globalization, development is often focused on the economic sector as a primary measure of success. One of the critical indicators of national development success is economic growth. Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic development, including in Sidoarjo Regency. This study aims to analyze MSME development policies as a cornerstone of strengthening the local economy. Using a descriptive-qualitative approach, the study evaluates the effectiveness of local government policies, encompassing aspects such as financing, skill training, market access, and digitalization. The results show that although government policies have contributed positively, significant challenges remain that hinder the optimal role of MSMEs. These challenges include limited access to financial resources, low technology adoption, and insufficient collaboration between MSME actors and other stakeholders. On the other hand, local potentials such as handicrafts, food processing, and the creative sector have yet to be fully utilized. Recommendations from this study include enhancing synergy between the government, business actors, and local communities, providing incentives for technology-based innovation, and strengthening business networks through digital platforms. With more targeted policies and active participation from all parties, MSME development in Sidoarjo is expected to boost local economic competitiveness and create inclusive and sustainable development.